A Novel Polishing Paste (Mollusk Shells) for Poly (Methylmethacrylate) - Nicole Guerra; Evelin Meneses; Stefany Caballero-García; Frank Mayta-Tovalino (Hindawi Limited, 2021)
Objective. The aim of this study was to evaluate the effectiveness of a mollusk shells polishing paste (Donax obesulus) on the surface roughness of acrylic resin poly (methylmethacrylate) (PMMA). Methods. This study was an in vitro experimental design. A sample size of 72 was divided into 4 groups of n = 18 each. PMMA specimens were prepared and polished with the evaluated pastes using mollusk shells (experimental paste) and pumice stone. Surface roughness (μm) was measured using a profilometer after polishing the PMMA samples. The paired Wilcoxon test was used to evaluate the roughness values at 24 and 48 hours. Then, the Mann-Whitney U test was used to identify the differences between the effects of the two groups evaluated with a significance level of α = 0.05. Results. The roughness difference between the pastes under study was compared, and mean values of 0.50 ± 0.07 μm (mollusk shell paste group) and 0.45 ± 0.12 μm (pumice group) were obtained. No statistically significant differences were found between the experimental paste and pumice stone paste p=0.309. The specimens polished with pumice stone paste showed higher roughness values, while those polished with the experimental paste exhibited the lowest values. Conclusion. In summary, mollusk shells polishing paste had a decrease in roughness values compared to pumice, although these differences were not statistically significant.